Deciphering of the Human Interferon-Regulated Proteome by Mass Spectrometry-Based Quantitative Analysis Reveals Extent and Dynamics of Protein Induction and Repression - Megger, Dominik A.; Philipp, Jos; Le-Trilling, Vu Thuy Khanh; Sitek, Barbara; Trilling, Mirko (Frontiers in Immunology, 2017)
Interferons (IFNs) are pleotropic cytokines secreted upon encounter of pathogens and tumors. Applying their antipathogenic, antiproliferative and immune stimulatory capacities, recombinant IFNs are frequently prescribed as drugs to treat different diseases. IFNs act by changing the gene expression profile of cells. Due to characteristics like rapid gene induction and signaling, IFNs also represent prototypical model systems for various aspects of biomedical research (e.g. signal transduction). In regard to the signaling and activated promoters, IFNs can be subdivided into two groups. Here, alterations of the cellular proteome of human cells treated with IFNalpha and IFNgamma were elucidated in a time-resolved manner by quantitative proteome analysis. The majority of protein regulations were strongly IFN type- and time-dependent. In addition to the expected upregulation of IFN-responsive proteins, an astonishing number of proteins became profoundly repressed especially by IFNgamma. Thus, our comprehensive analysis revealed important insights into the human interferome and its dynamics of protein induction and repression. Interestingly, the new class of IFN-repressed genes (IRepGs) comprises known host factors for highly relevant pathogens like HIV, Dengue Virus and Hepatitis C Virus.